Nomenclatural notes on Acanthophyllum (Caryophylleae, Caryophyllaceae) - Pirani, Atefeh; Rabeler, Richard K. (Phytotaxa, 2017)
Acanthophyllum Meyer (1831: 210) in a broad sense comprises 80–90 perennial subshrubby species which are distributed mainly in the Irano-Turanian region (see e.g., Bittrich 1993, Ghaffari 2004, Pirani et al. 2014). According to the phylogenetic study by Pirani et al. (2014), Acanthophyllum s.lat. includes 11 sections. As part of our ongoing taxonomic investigations of Acanthophyllum, corrections to names of five Acanthophyllum sections are made here.